Towards a positive pedagogy: designing pedagogical practices that facilitate positivity within the classroom. Issue 3 (27th May 2018) - O'Brien, Mia; Blue, Levon
Abstract: Students flourish by having positive learning experiences at school. Here we describe an action research study undertaken in an Australian primary school that was intended to promote the development of students' positive learning identities and resources. We partnered with classroom teachers to devise pedagogical practices that explicitly targeted the development of students' positive cognitions, positive emotions and positive experiences. Two main lines of inquiry guided the action research: (i) what might 'positivity' look like in relation to learning, for students within primary school classrooms? and (ii) what kinds of pedagogical practices promote positivity within the classroom? Data were collected over an 18-month period and drew from two cycles of action research which generated teacher reflections and interviews, observations of classroom teaching and learning episodes, rich descriptive field notes, anecdotal feedback from parents, as well as student reflections and student focus group interviews. Practice theory was used to analyse the data. Our findings indicate that there are explicit learning behaviours and dispositions that represent positivity in a learning context; and we identify pedagogical practices effective for fostering these behaviours and dispositions. These practices, referred to here as positive pedagogies, include teacher talk, social and emotional resources for students, the supplementation of lessons with resource building materials and the development of individualised learning goals that target the development of positive cognitions, emotions and experiences. We provide a detailed commentary of the action research cycles (and related professional learning) that classroom teachers undertook in the process of contributing to the 'positive pedagogies' presented.